Establishment of virtual education classes as an effort to prevent stunting in Sutera Village, Sukadana District - Isra Mahendra; Selviana Selviana; Shelly Ayu Andesty; Nanda Aulia Ramadayanti; Decha Suci Amelia; Safriansyah Safriansyah (Community Empowerment, 2021)
Sutera Village is one of the villages with a high stunting rate located in North Kayong Regency. The stunting cadres that had been formed previously were unable to carry out their duties due to the Covid-19 pandemic. Finally, the prevention model on stunting nutrition problems in the Covid-19 pandemic era was created with the idea of ​​forming virtual classes for stunting cadres through various communication applications using video. The purpose of this community service is to create educational media for cadres as an effort for stunting prevention in Sutera Village, Sukadana District, North Kayong Regency. Education model was carried out with direct learning and virtual with promotional media such as nutritional calendars, learning books, games, educational materials, stunting symptom forms, and video tutorials for monitoring child nutrition. The Wilcoxon test shows the p-value of 0.004 for the knowledge variable and 0.016 for attitude. So, it was concluded that there was an increase in knowledge and attitudes. In other words, the establishment of virtual education classes as an effort to prevent stunting in Sutera Village, Sukadana District, North Kayong Regency is effective in increasing the knowledge and attitudes of stunting cadres.